Comparison of Public Sector Service Quality - Clara Rizky Triani Rauf; Andi Juanna (Jambura Science of Management, 2019)
This study aims to obtain information, information, and data about things that have not been previously known. This study examined and analyzed how the Comparison of Service Quality in the Delivery Unit of the Prof.Dr.H.Aloe Saboe Regional General Hospital and Toto Kabila Gorontalo Hospital. The population in this study were visitors at the Public Hospital Unit of Prof.Dr.H.Aloei Saboe and Toto Kabila Hospital. In this study the number of samples used was 80 respondents. In determining the sample, the sampling technique used is the accidental sampling technique. The reference used to measure whether there is a difference between service quality received and expected by visitors is the 5 dimensions of service quality (tangible, reliability, responsiveness, assurance, empathy). The results showed that the significance value (sig-2 tailed) was 0.002 for perception. At the 5% significance level the value is significant because the significance is 0,000 0,05, so it is concluded that there are differences in perceptions of service quality of Rs Aloe Saboe and Rs Toto Kabila so that H1 is accepted. The results of the independent analysis of sample t-test of significance value (sig-2 tailed) amounted to 0,000 for expectations. At the 5% significance level the value is significant because the significance is 0,000 0,05, so it is concluded that there are differences in service quality expectations of Rs Aloe Saboe and Rs Toto Kabila so H2 is accepted.